2000
DOI: 10.1021/ol991360y
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Capped π-Prismands:  Syntheses and Conformational Analyses

Abstract: [structure: see text] The one-pot syntheses of the new diazabicyclophanes 5-7 are described. The benzene rings incorporated in the bridging chains exhibit rotational motion which is examined by means of variable-temperature NMR experiments and semiempirical calculations. X-ray analysis and NMR studies indicate that the metal ion in the endohedral silver(I) complex of 7 fluctuates between the two nitrogen atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 19 publications
(19 reference statements)
3
31
0
Order By: Relevance
“…The copper-nitrogen distances are expanded with regard to copper(i) amine complexes (average [a] X = S for 4, 7-9, 11; X = Se for 5; X = O for 6. value 2.18 Å) [26] but comparable to those reported for 2·Cu + (2.11 Å). [9] The distance Cu-S (2.52 Å) is longer than those reported in other thioether-Cu I complexes (2.25-2.30 Å). [27] The molecular structure of 5·Cu + is isomorphous to that of 4·Cu + .…”
Section: (C) Formation Of Metal Complexesmentioning
confidence: 90%
See 2 more Smart Citations
“…The copper-nitrogen distances are expanded with regard to copper(i) amine complexes (average [a] X = S for 4, 7-9, 11; X = Se for 5; X = O for 6. value 2.18 Å) [26] but comparable to those reported for 2·Cu + (2.11 Å). [9] The distance Cu-S (2.52 Å) is longer than those reported in other thioether-Cu I complexes (2.25-2.30 Å). [27] The molecular structure of 5·Cu + is isomorphous to that of 4·Cu + .…”
Section: (C) Formation Of Metal Complexesmentioning
confidence: 90%
“…These values are about 0.2 Å larger than those reported for 2·Ag + . [9] In the case of 7·Ag + it was possible to measure the wave number for the stretching vibration of the triple bond (ν = 2281 and 2206 cm -1 ). These values are shifted towards lower energy as compared to the free ligand (ν = 2293 and 2231 cm -1 ) which is evidence for an interaction between the metal and the triple bonds.…”
Section: (C) Formation Of Metal Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gleiter et al reported that torsional motion in related nitrogen-based systems is frozen out at À20 8C and the rotation of the p systems ceases at À82 8C. [20] [ 1 H NMR spectroscopy. The robustness of the [As 2 L 3 ] assembly is exciting for several reasons.…”
mentioning
confidence: 99%
“…[20,23] The self-assembly strategy allows for increased yields in the macrobicyclization reaction and is a proof of principle of the design strategy to form arsenic-based supramolecular assem- Zuschriften blies from simple, identical starting compounds. The success of this strategy augurs well for the formation of larger arsenicbased capsules resulting from expanded two-and threefold symmetric ligands.…”
mentioning
confidence: 99%